Pengaruh Respon Governor Elektronik Pada Operasi Pembangkit Listrik Tenaga Panas Bumi dengan Memperhatikan Kendala Operasi - Jakariya - (Energi & Kelistrikan, 2023)
Geothermal Power Center is a power plant with renewable energy. Basically, PLTP is a power plant whose raw materials come from the bowels of the earth in the form of hot steam. This steam is obtained from several wells which are then channeled through a transmission pipe system to the PLTP unit. after arriving at the PLTP the steam is controlled and regulated, and the pressure is then channeled to the steam turbine which rotates the electric generator. This research discusses the response of the electronic governor when the system frequency drops which affects the work of the Kamojang PLTP unit 4 equipment. From various methods applied it is evident that when the system frequency drops all PLTP equipment is disrupted, especially the condenser level where the pressure increases from 780 mmH2O to 1023 mmH20. this can cause the turbine to trip so that it needs to be responded to properly by maneuvers on the operating side so that the generator is able to survive under conditions of system frequency disturbances down.